ANALISIS HILANGNYA HAK WARIS BAGI AHLI WARIS ATAS AKIBAT PERBUATAN MELAWAN HUKUM PENGUASAAN HARTA WARISAN SECARA SEPIHAK (Contoh Kasus Putusan No: 601/Pdt.G/2019/PN. Jkt.Pst) - Muhammad Hadlisina Hawari; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Inheritance law is a subset of family law that is heavily influenced by social conditions. Indonesia does not have a single inheritance law due to its pluralistic existence. If an heir's inheritance rights are violated, he has the right to sue. The judge agreed not to grant compensation to the defendant in his judgment No: 601/Pdt.G/2019/PNJkt.Pst, and in the case of an act committed by the defendant, he nevertheless received a percentage of the inheritance, despite the fact that the act he committed had already violated the provisions of Article 838 of the Civil Code. Normative analysis was used as a research tool. The findings revealed that an heir who had been found to have committed an act considered unacceptable as described by Article 838 of the Criminal Code should no longer be eligible to inherit. This is the condition where the judge can decide thus, because the case refers to the Civil Law which is a family law which is very likely in terms of its forgiving element. Furthermore, the judge instructed the defendants to prove an illegal act in a criminal context first, so that the facts at the Civil Court trial would be clearer and could be considered by the judge while making decisions in court in a civil context.